Chirality-Induced Suppression of Singlet Oxygen in Lithium-Oxygen Batteries with Extended Cycle Life - Chae, Kyunghee; Kim, Youngbi; Oh, Yookyeong; Hahn, Hosik; Son, Jaehyun; Kim, Youngsin; Kim, Hyuk-Joon; Lee, Hyun Jeong; Jang, Dohyub; Moon, Jooho; Kang, Kisuk; Han, Jeong Woo; et al. (Shanghai Jiao Tong University Press, 2025)
Lithium-oxygen (Li-O-2) batteries are perceived as a promising breakthrough in sustainable electrochemical energy storage, utilizing ambient air as an energy source, eliminating the need for costly cathode materials, and offering the highest theoretical energy density (similar to 3.5 kWh kg(-1)) among discussed candidates. Contributing to the poor cycle life of currently reported Li-O-2 cells is singlet oxygen (O-1(2)) formation, inducing parasitic reactions, degrading key components, and severely deteriorating cell performance. Here, we harness the chirality-induced spin selectivity effect of chiral cobalt oxide nanosheets (Co3O4 NSs) as cathode materials to suppress O-1(2) in Li-O-2 batteries for the first time. Operando photoluminescence spectroscopy reveals a 3.7-fold and 3.23-fold reduction in O-1(2) during discharge and charge, respectively, compared to conventional carbon paper-based cells, consistent with differential electrochemical mass spectrometry results, which indicate a near-theoretical charge-to-O-2 ratio (2.04 e(-)/O-2). Density functional theory calculations demonstrate that chirality induces a peak shift near the Fermi level, enhancing Co 3d-O 2p hybridization, stabilizing reaction intermediates, and lowering activation barriers for Li2O2 formation and decomposition. These findings establish a new strategy for improving the stability and energy efficiency of sustainable Li-O-2 batteries, abridging the current gap to commercialization.